Sexual dimorphism, gonad structure and genetic differences of pink skunk clownfish (Amphiprion perideraion) - QL 638 .P77 S3 2010 (Institut Akuakultur Tropika, 2011)
Pink Skunk Clownfish, Amphiprion perideraion, is known as protandric hermaphrodite where it can change its sex from male to female. In order to breed clownfishes in captivity, they need to be paired which means the ability to identify the fish sex is crucial. This becomes the bottleneck for the production of A. perideraion in captivity since breeders have failed to differentiate the sex of the wild fish collected.